Bilateral Radial Ulnar Synostosis and Vertebral Anomalies in a Child with a De Novo 16p13.3 Interstitial Deletion. (1st July 2013) - Tam, Allison; Lee, Kit Shan; Lee, Sansan; Burkhalter, William; Pascua, Lucio U.; Slavin, Thomas P.
Abstract : We describe an 8-year-old boy with developmental delay, clinical bilateral radial ulnar synostosis, Klippel-Feil anomaly, and other vertebral deformities who was found to have a de novo deletion of 114.5kb at 16p13.3. The deletion contains five genes and three miRNAs. The genes are E4F1, DNASE1L2, ECI1, RNPS1, and ABCA3 ; miRNAs are MIR3677, MIR940, and MIR4717. The specific deletion has never been previously reported. We describe the phenotype of the boy and review the genes in the deleted region. None of the regulatory elements have any known linkage to skeletal formation and/or maintenance. We believe this deletion is causative given that it was de novo and that this patient cannot be easily explained as having any other specific recognizable pattern of human malformation.